Porous silicon nanoneedles modulate endocytosis to deliver biological payloads - Gopal,S; Chiappini,C; Penders,J; Leonardo,V; Seong,H; Rothery,S; Korchev,Y; Shevchuk,A; Stevens,MM (Advanced Materials, 2019)
Owing to their ability to efficiently deliver biological cargo and sense the intracellular milieu, vertical arrays of high aspect ratio nanostructures, known as nanoneedles, are being developed as minimally invasive tools for cell manipulation. However, little is known of the mechanisms of cargo transfer across the cell membranenanoneedle interface. In particular, the contributions of membrane piercing, modulation of membrane permeability and endocytosis to cargo transfer remain largely unexplored. Here, combining stateoftheart electron and scanning ion conductance microscopy with molecular biology techniques, it is shown that porous silicon nanoneedle arrays concurrently stimulate independent endocytic pathways which contribute to enhanced biomolecule delivery into human mesenchymal stem cells. Electron microscopy of the cell membrane at nanoneedle sites shows an intact lipid bilayer, accompanied by an accumulation of clathrincoated pits and caveolae. Nanoneedles enhance the internalization of biomolecular markers of endocytosis, highlighting the concurrent activation of caveolae and clathrinmediated endocytosis, alongside macropinocytosis. These events contribute to the nanoneedlemediated delivery (nanoinjection) of nucleic acids into human stem cells, which distribute across the cytosol and the endolysosomal system. This data extends the understanding of how nanoneedles modulate biological processes to mediate interaction with the intracellular space, providing indications for the rational design of improved cellmanipulation technologies.